Introduction to the Physics of Gyrotrons - Nusinovich, Gregory S. (Johns Hopkins University Press, 2004)
As unique sources of coherent high-power, microwave, and millimeter-wave radiation, gyrotrons are an essential part of the hunt for controlled fusion. Presently, gyrotrons are actively used for electron cyclotron resonance plasma heating and current drive in various controlled fusion reactors. These sources have been under development in many countries for more than forty years. In spite of their widespread use, however, there is as yet no single book to introduce non-specialists to this vital field.Now Gregory S. Nusinovich, an early pioneer of the gyrotron and widely regarded today as the world's leading authority on the subject, explains the fundamental physical principles upon which gyrotrons and related devices operate. Nusinovich first sets forth some "rules of thumb" that allow readers to understand gyrotron operation in simple terms. He then explores the fundamentals of the general theory of gyrotrons and offers an overview of the various types of gyro-devices, including gyromonotrons, gyroklystrons, gyro-traveling-wave tubes, and gyrotwystrons. He explains not only the theory, linear and nonlinear, but also the practical challenges that users of such devices face. This book will be of interest to undergraduate and graduate students as well as to those who develop gyrotrons or who use them in various applications. It should also appeal to plasma physicists interested in charged-particle dynamics, as well as to applied physicists needing to know more about micro- and millimeter-wave technologies.